1975
DOI: 10.1083/jcb.67.3.852
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of proteins across membranes. II. Reconstitution of functional rough microsomes from heterologous components.

Abstract: The data presented in this paper demonstrate that native small ribosomal subunits from reticulocytes (containing initiation factors) and large ribosomal subunits derived from free polysomes of reticulocytes by the puromycin-KCI procedure can function with stripped microsomes derived from dog pancreas rough microsomes in a protein-synthesizing system in vitro in response to added lgG light chain mRNA so as to segregate the translation product in a proteolysis-resistant space. No such segregation took place for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
485
1
3

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,129 publications
(507 citation statements)
references
References 7 publications
18
485
1
3
Order By: Relevance
“…Blobel in 1971 formulated the "signal hypothesis" and postulated that protein secretion out of a cell requires an intrinsic signal (N-terminal signal sequence) that governs translocation across membranes [11,12]. Several functional interactions of the signal sequence with the eukaryotic translocation apparatus have been defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blobel in 1971 formulated the "signal hypothesis" and postulated that protein secretion out of a cell requires an intrinsic signal (N-terminal signal sequence) that governs translocation across membranes [11,12]. Several functional interactions of the signal sequence with the eukaryotic translocation apparatus have been defined.…”
Section: Discussionmentioning
confidence: 99%
“…The 23 amino acid leader sequence of RS (Fig-1A) possesses all the structural and functional features associated with eukaryotic signal sequences [10], including a polar (n) region with a net positive charge on its N-terminal side, a central hydrophobic core (h) region and a polar (c) region at C-terminal side with a signal peptidase cleavage site. These structural features of signal sequence serve as a platform on which the signal peptidase and signal recognition particles interact and cleave the 23 amino acid leader peptide from the nascent protein during the translocation of the polypeptide chain into the lumen of the endoplasmic reticulum [11,12]. The folding of the RS subunit with the formation of intramolecular disulfide bonds and the assembly of RS subunits into RS dimer and octamer take place at this stage [13].…”
mentioning
confidence: 99%
“…Signal peptides serve as a sorting signal that targets nascent secretory proteins to sites of translocation on the ER membrane, where it is subsequently proteolytically removed from the mature chain by signal peptidase. 27,28 Signal peptides do not contain specific amino-acid residues and are variable in length (15 to as many as 50 amino acids). Kaiser et al 29 reported that many random sequences can functionally replace the secretion signal sequence of yeast invertase.…”
Section: Discussionmentioning
confidence: 99%
“…La première percée cruciale qui a fait entrer la voie de Palade dans l'ère moléculaire s'est faite avec la publication en 1975 par le protégé de Palade, Gunther Blobel, d'un système acellulaire qui reproduisait la traduction et la translocation du précurseur d'une protéine de sécrétion vers l'intérieur de membranes du RE isolées ; deux articles dans le Journal of Cell Biology ont posé les premiers jalons pour comprendre le mécanisme du lien entre la synthèse protéique et le cheminement vectoriel des protéines sécrétoires vers ce quiétait sûrement une protéine-canal hydrophile dans le RE (Blobel & Dobberstein, 1975a, 1975b Singer aété très excité par la découverte de Blobel, car celle-ciétayait son point de vue selon lequel la mise en place de l'asymétrie des protéines dans la membrane devait dépendre d'un canal spécial dans le RE chargé de transporter les séquences protéiques hydrophilesà travers la bicouche hydrophobe. Pourtant Singer restait sceptique quantà la possibilité pour la stratégie de reconstitution biochimique d'apporter une explication approfondie du processus.…”
Section: Etudier Les Membranes Biologiques Comme Un Assemblage Macromunclassified